DISEÑO DE LOFTS RETRÁCTILES DE USO MIXTO PARA LA CIUDAD DE GUAYAQUIL. - Ortega Torres, María José. (2020)
The thesis project consists of a proposal of the design of retractable lofts of mixed use for the city of Guayaquil from the demolition of a disabled building in downtown. The purpose of the project is to establish a new concept of mixed multifunctional housing as part of the urban reintegration of the sector, implementing the retractable mechanism to transform the spaces according to the need for office or housing, previously identifying the types of demolitions to apply to the current building to determine the appropriate one. The proposal of the building will allow the reactivation of the residential aspect of downtown Guayaquil, providing living spaces that also work as an office to integrate the existing commercial and economic activity, attracting young entrepreneurs seeking to become independent and enter the labor world. For further information on intervention in the area, professionals in the field of Engineering and Architecture were interviewed, with their focus on soils and history. Additionally, surveys were conducted to citizens, categorized as young adults, to support applicable interests and criteria. As a result, the project responds to the needs and interests of a new community through a bioclimatic and innovative design